Impact of sodium nitrate on astaxanthin production in green micro- alga Haematococcus pluvialis under laboratory condition - Singh, Surendra; Tiwari, Nisha (International Journal of Scientific Research in Biological Sciences, 2020)
There is currently much interest in biological active compound derived from natural resources, especially compounds that can efficiently act on molecular targets, which are involved in various diseases. Astaxanthin is a xanthophyll carotenoid which is found in various micro-organisms and marine animals. astaxanthin is used as a pigment in aquaculture and food industries and has application in pharmaceutical and nutraceutical due to its high antioxidant activity. In addition, astaxanthin has important metabolic function including enhancement of immune reponses and protection against disease such as cancer. Haematococcus pluvialis is the richest source of natural astaxanthin and is now cultivated at industrial scale. Therefore, the main objective of this study was to observe the production of astaxanthin at different concentration of Nitrogen in Haematococcus pluvialis. The experiment was conducted for 18 days and data were analyzed at the interval of 2 days, the maximum concentration of carotenoid was recorded in Haematococcus pluvialis is 1.646µgmL-1 on 8th day at 20mM concentration of Sodium Nitrate.